Analisis Pengendalian Kualitas Produk Dengan Metode Statistical Quality Control (SQC) Pada Perusahaan Roti Aldina Bakery Kota Tasikmalaya - Lutfiah Sahara; Suci Putri Lestari; Barin Barlian (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The bread Company Aldina Bakery is a company that produces white bread. The fundamental problem of this company is damaged products due to a poor quality control system. The purpose of this study is to identify the nature of the damage, analyze the application of the Statistical Quality Control (SQC) method and recommend actions. The steps include filling out research forms, making histograms, making Pareto charts, making and calculating Pareto charts, and making cause and effect diagrams. The results showed that there were three types of damage, namely scorched defects, size defects and flaking skin defects. The results of the analysis using a causal diagram show that the causes of poor light bread are labor, methods, materials and machines. The Pareto diagram shows that the type of product damage is more dominant in scaly shell damage in one year to 3,296 units. The results of the control chart analysis show that Aldina Bakery's quality control is still not under control. The next step to reduce the risk of defects in the product is to make a Standard Operating Procedure (SOP), modify the oven by adding a timer and temperature, make molds according to standards by considering raw bread ingredients, and coat the molds with margarine evenly to prevent sticking